Comparative Impact of Virtual and Face-To-Face Education on the Academic Performance and Perception of Accounting Students at a Peruvian University during the Pandemic - Salazar, Carlos Alberto Hinojosa; Escobar , Benjamín Roldán Polo; Pelaez , Heisely Mori; Fernández , Juan Manuel Buendía; Acosta , Robert Wagner Ocadio; Camacho , Consuelo González (Journal of Ecohumanism, 2024)
The present study compares the impact of virtual and face-to-face education modalities on the academic performance and perception of accounting students at the Universidad Nacional Toribio Rodríguez de Mendoza de Amazonas during the COVID-19 pandemic. Through a mixed methodological approach, quantitative and qualitative data from 98 students were analyzed, evaluating their academic performance, interaction, feedback and satisfaction in both modalities. The results show that students in the virtual modality obtained higher academic performance, attributed to the flexibility of online education. However, interaction and feedback were perceived as more effective in the face-to-face modality. Students valued the flexibility of virtual education, but emphasized the importance of personal interaction and the traditional classroom environment to maintain concentration and academic engagement. This study concludes that both modalities have strengths and weaknesses, and suggests that a hybrid combination could offer a more complete educational experience. Improvements in feedback and assessment in virtual environments are recommended, as well as encouraging active participation through interactive technologies.